2000
DOI: 10.1046/j.1440-1622.2000.01802.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric resection in the aged (≥ 80 years) with gastric carcinoma: a multivariate analysis of prognostic factors

Abstract: Results indicate that gastric cancer in elderly patients has a poorer prognosis than that in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 20 publications
3
36
2
8
Order By: Relevance
“…It is generally documented that gastric cancer in elderly patients is predominantly localized to the lower third of the stomach [6][7][8][9][14][15][16][17][18]. Previous reports demonstrated that the proportion (range, 42%-63%) of carcinomas in the lower third of the stomach in the elderly was higher than the proportion (range, 31%-44%) in the young [3,[6][7][8][9][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is generally documented that gastric cancer in elderly patients is predominantly localized to the lower third of the stomach [6][7][8][9][14][15][16][17][18]. Previous reports demonstrated that the proportion (range, 42%-63%) of carcinomas in the lower third of the stomach in the elderly was higher than the proportion (range, 31%-44%) in the young [3,[6][7][8][9][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated that the proportion (range, 42%-63%) of carcinomas in the lower third of the stomach in the elderly was higher than the proportion (range, 31%-44%) in the young [3,[6][7][8][9][14][15][16][17][18][19]. Our data confirmed that, in patients aged 85 years or older, cancers were situated more often in the lower third of the stomach compared with the younger age groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kubota et al observed a higher, but statistically not significant, postoperative complications rate in octogenarian patients with curatively resected cancer and a postoperative mortality rate similar to that of patients aged 40-79 [50]. Kunisaki et al noted higher incidence of postoperative morbidity in the elderly among all registered patients-curatively and palliative resected [51].…”
Section: Japanese and Far East Studiesmentioning
confidence: 97%